+0  
 
0
230
2
avatar

Please expand the following at x = 0:  sqrt(1 + x)^ -1. Thank you for help.

Guest Jul 20, 2017
 #1
avatar+87333 
+1

 

 (1 + x)^ -1/2  at x = 0

 

Using the Maclaurin Series, we have

 

f(0) + f ' (0)x  + f ''(0) x^2 / 2!  +   f  '''(0) x^3 / 3! + ......  + f(n)(0) x^n / n!

 

f(0)  =  1

 

f ' (x) =  ( -1/2) (1 + x)^( -3/2)   and   f ' (0)  =  (-1.2)  ( 1 + 0)^-(3/2)=   (-1/2)

 

f '' (x)  =  (3/4) (1 + x) ^(-5/2)  and   f '' (0)  = (3/4)  (1 + 0)^(-5/2)  =   (3/4)

 

f ''' (x)  =   (-15 / 8 ) ( 1 + x)^(-7/2)   and  f''' (0)  = (-15/8) (1 + 0)^(-7/2)  = ( - 15 / 8)

 

 

So we have the first four terms

 

1 - (1/2)x + (3/4)x^2/2   - (15/8)x^3 / 6 + ..... +  f(n)(0) x^n / n!  =

 

1 - x/2  + 3x^2/8  - 15x^3/48 + .....+  f(n)(0) x^n / n!  =

 

1 - x/2  + 3x^2/8  - 5x^3/16 + ...... +  f(n)(0) x^n / n!

 

 

 

cool cool cool

CPhill  Jul 20, 2017
 #2
avatar
0

sqrt(1 + x)^ -1 =1 - 1/2x + [1.3/2.4]x^2 - [1.3.5/2.4.6]x^3 + [1.3.5.7/2.4.6.8]x^4.........etc.

Guest Jul 20, 2017

4 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.